Pengaruh Penerapan Model Pembelajaran Generatif terhadap Kemampuan Penalaran Matematis Peserta Didik Kelas VIII SMPN 1 Payakumbuh Tahun Pelajaran 2019/2020 - SYAFIRA NURUL HUDA (Jurnal Edukasi dan Penelitian Matematika, 2019)
The ability of Mathematical reasoning is one of seven mathematical learning objectives that must be achieved. However, the mathematical reasoning ability of students is still not optimal. One of the efforts to improve students' mathematical reasoning ability is to apply generative learning models, aimed at describing whether the mathematical reasoning abilities of students who learn with generative learning models are better than the Mathematical reasoning abilities of students who learn with conventional learning. This research is a combination of descriptive and quasy experiment research with Randomized Control-Group Only Design research design. Based on the results of data analysis by doing t-test, it shows that the mathematical reasoning ability of students who learn using generative learning models is better than the mathematical reasoning ability of students who learn to use conventional learning in class VIII of SMPN 1 Payakumbuh. Keywords – Mathematical Reasoning, Generative Learning Model, Conventional Learning